NLRP1 inflammasome involves in learning and memory impairments and neuronal damages during aging process in mice - Sun, Dan; Gao, Guofang; Zhong, Bihua; Zhang, Han; Ding, Shixin; Sun, Zhenghao; Zhang, Yaodong; Li, Weizu (Behavioral and brain functions, 2021)
Background Brain aging is an important risk factor in many human diseases, such as Alzheimer’s disease (AD). The production of excess reactive oxygen species (ROS) mediated by nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2) and the maturation of inflammatory cytokines caused by activation of the NOD-like receptor protein 1 (NLRP1) inflammasome play central roles in promoting brain aging. However, it is still unclear when and how the neuroinflammation appears in the brain during aging process. Methods In this study, we observed the alterations of learning and memory impairments, neuronal damage, NLRP1 inflammasome activation, ROS production and NOX2 expression in the young 6-month-old (6 M) mice, presenile 16 M mice, and older 20 M and 24 M mice. Results The results indicated that, compared to 6 M mice, the locomotor activity, learning and memory abilities were slightly decreased in 16 M mice, and were significantly decreased in 20 M and 24 M mice, especially in the 24 M mice. The pathological results also showed that there were no significant neuronal damages in 6 M and 16 M mice, while there were obvious neuronal damages in 20 M and 24 M mice, especially in the 24 M group. Consistent with the behavioral and histological changes in the older mice, the activity of β-galactosidase (β-gal), the levels of ROS and IL-1β, and the expressions of NLRP1, ASC, caspase-1, NOX2, p47phox and p22phox were significantly increased in the cortex and hippocampus in the older 20 M and 24 M mice. Conclusion Our study suggested that NLRP1 inflammasome activation may be closely involved in aging-related neuronal damage and may be an important target for preventing brain aging.